Multilevel Cryptography Model using RC5, Twofish, and Modified Serpent Algorithms - Hoobi, Mays M. (Iraqi Journal of Science, 2024)
Due to the rapid development of digital communication systems, information security is now essential for both the storage and exchange of data. Security has become a key research axis as a result of the rapid evolution of network technologies. The transmission of digital data is necessary for various forms of communication. Particularly in applications requiring a high level of security, like surveillance applications, military applications, biometric applications, and radar applications, where this transmission should be secure. Thus, data is normally encoded through the technique of encryption to prevent unauthorized access. The current imperative is for cyber security to guarantees the integrity and confidentiality of data transmission over the internet and offer defense against hostile attacks. To ensure the security and dependability of digital data transmission, the goal of this research is to create and analyze a robust multilevel cryptography model using three cases. Those cases include: case 1 utilized the RC5 algorithm only. Case 2 examined the use of RC5 together with the Twofish algorithms, and case 3 employed a combination of three effective algorithms in sequential order (RC5 with Twofish and Modified Serpent). The results were analyzed and showed that case 3—which encrypts data by applying three effective algorithms sequentially—is preferable. This case offers a performance model for various combinations of the symmetric key cryptography algorithms RC5, Twofish, and modified Serpent. Utilizing analysis tools including entropy, floating frequency, histogram, autocorrelation, and brute force attack, the three cases were compared.